γδ TCR T lymphoblastic leukemia in a child presenting with marked hyperleukocytosis - Mass, Jirong (Clin Case Rep, 2021)
γδ TCR T lymphoblastic leukemia is rare in children and should be differentiated mainly from hepatosplenic T‐cell lymphoma in this age group.